Distributed renewable energies for off-grid communities : strategies and technologies toward achieving sustainability in energy generation and supply - El Bassam, Nasir; Maegaard, Preben; Schlichting, Marcia Lawton (Amsterdam : Elsevier, 2013)
It is estimated that more than two billion people worldwide lack access to modern energy resources. Renewable energy has the potential to bring power to these many communities and individuals who function off the grid. This book describes the latest advances in distributed and off-grid renewable energy technologies and offers strategies and guidelines for planning and implementation of sustainable, decentralized energy supply. Coverage includes wind, solar, geothermal, and biomass systems planning and integration, economic assessment models and the role of legislative structures. -- Back Cover
Restructuring future energy generation and supply -- Road map of distributed renewable energy communities -- Planning of integrated renewable communities -- Determination of community energy and food requirements -- Energy basics, resources, global contribution and applications -- Solar energy -- Wind energy -- Biomass and bioenergy -- Hydropower -- Marine energy -- Geothermal energy -- Energy storage, smart grids and electric vehicles -- Current distributed renewable energy rural and urban communities -- Ownership, citizens participation and economic trends.
Includes bibliographical references (p.333 - 341) and index.
Keywords: Small power production facilities; Distributed generation of electric power; Renewable energy sources; Electric power distribution; Energy development